Impact of Branched-Chain Amino Acid Catabolism on Fatty Acid and Alkene Biosynthesis in Micrococcus luteus - Surger, Maximilian J.; Angelov, Angel; Stier, Philipp; Übelacker, Maria; Liebl, Wolfgang (Frontiers in Microbiology, 2018)
Micrococcus luteus naturally produces olefins (unsaturated aliphatic hydrocarbons) and represents a promising host to produce hydrocarbons as constituents of biofuels and lubricants. In this work, we identify the genes for key enzymes of the branched chain amino acid catabolism in M. luteus, whose first metabolic steps lead also to the formation of primer molecules for branched chain fatty acid and olefin biosynthesis, and demonstrate how these genes can be used to manipulate the production of specific olefins in this organism. We constructed mutants of several gene candidates involved in the branched chain amino acid metabolism or its regulation and investigated the resulting changes in the cellular fatty acid and olefin profiles by GC/MS. The gene cluster encoding the components of the branched chain α-keto acid dehydrogenase (BCKD) complex was identified by deletion and promoter exchange mutagenesis. Overexpression of the BCKD gene cluster resulted in about threefold increased olefin production whereas deletion of the cluster led to a drastic reduction in branched chain fatty acid content and a complete loss of olefin production. The specificities of the acyl-CoA dehydrogenases of the branched amino acid degradation pathways were deduced from the fatty acid and olefin profiles of the respective deletion mutant strains. In addition, growth experiments with branched amino acids as the only nitrogen source were carried out with the mutants in order to confirm our annotations. Both the deletion mutant of the BCKD complex, responsible for the further degradation of all three branched chain amino acids, as well as the deletion mutant of the proposed isovaleryl-CoA dehydrogenase (specific for leucine degradation) were not able to grow on leucine in contrast to the parental strain. In conclusion, our experiments allow the unambigous assignment of specific functions to the genes for key enzymes of the branched chain amino acid metabolism of M. luteus. We also show how this knowledge can be used to engineer the isomeric composition and the chain lengths of the olefins produced by this organism.